WORK LIFE BALANCE IS IT A DUAL HORSE RIDE - Priyavarsha, R. (International Journal of Psychosocial Rehabilitation, 2020)
Unlike western nations, striking the perfect balance between work and personal life is still a distant dream in India. In the west, work-life balance is taken earnestly. With the steady rise in dual earning families this decade, achieving work-life balance is more of a struggle for a woman than a man in a conservative Indian family set up. Also, the steep increase in the number of single parent families in the society, has given a hard blow on work life balance.Changes in the organizational and personal front by utilizing modern technology can help in pursuing personal goals and maintaining an effective QWL (Quality of Work Life).